The Role of Interfascial Plane Blocks in Paediatric Regional Anaesthesia: A Narrative Review of Current Perspectives and Updates - Sujana Dontukurthy; Roshanak Mofidi (Anesthesiology Research and Practice)
Regional anaesthesia has been increasingly used for analgesia in the perioperative period in paediatric anaesthesia for better pain control and improved patient outcomes. Interfascial plane blocks are considered as a subgroup of peripheral nerve blocks. The advent of ultrasound in modern regional anaesthesia practice has led to the evolution of various interfascial plane blocks. The ease of their performance and the low complication rates, compared with neuraxial anaesthesia, have led to their increased use in the perioperative period. Interfascial plane blocks are often incorporated in the multimodal analgesia regimen in the early recovery and ambulation after surgery protocols for various chest wall and abdominal surgeries. This achieves better pain control and decreases the requirements of opioids in the perioperative period, thereby facilitating early mobilization and discharge. This narrative review focuses on the relevant anatomic considerations, technique for the performance of each block along with its current applications and limitations, and includes a review of the current literature on various interfascial plane blocks in paediatric regional anaesthesia.